Exploring the excellence of commercial Brahmi products from Thai online markets: Unraveling phytochemical contents, antioxidant properties and DNA damage protection - Junya Nopparat; Kawee Sujipuli; Kumrop Ratanasut; Monthana Weerawatanakorn; Surisak Prasarnpun; Bussagon Thongbai; Walailak Laothaworn; Phithak Inthima (Heliyon, 2024)
Brahmi (Bacopa monnieri (L.) Wettst.) is extensively used as a nutritional supplement in various commercial products as the plant contains abundant phytochemicals and has antioxidant properties. This study assessed the phytochemical contents, antioxidant properties, and DNA damage protection among seven Brahmi products sold through Thai online markets. Results showed that the P6 sample exhibited 3.5–7.5 fold higher bacoside contents than values observed in the other six product samples. The P6 sample also demonstrated the highest TTC, TFC, and TPC compared to the other brands. For antioxidant activity, the samples (P1–P7) displayed high capacity to scavenge DPPH free radicals with slightly significant differences ranging from 78.37 ± 0.25 to 87.21 ± 0.05 at p-value ≤0.01. The P6 sample showed strong protection against H2O2-induced oxidation of DNA strand breakage, indicating highly potent phytochemical compounds with effective free radical scavenging activity, and the ability to prevent DNA damage. The P6 sample showed promise as a valuable ingredient for the development of functional food products. However, further in vivo animal and clinical studies are required to explore the neuroprotective enhancement effects of Brahmi extracts.